Long-term trends in abundance, phenology, and morphometrics of Little Stint Calidris minuta during autumn migration in southern Sweden, 1946–2020 - Waldenström, Jonas; van Toor, Mariëlle; Lindström, Åke (Ornis Svecica, 2023)
The Little Stint Calidris minuta is an Arctic wader species that migrates through the Baltic Sea region towards wintering areas in North and West Africa and the Mediterranean region. We use a 75-year trapping series, comprising 4,791 Little Stints on autumn migration, from Ottenby Bird Observatory in Sweden to illustrate long-term trends in abundance, phenology, and morphometrics. Numbers of trapped juveniles dropped from median 31 (mean 74) in 1946–1999 to median 1.5 (mean 3.5) birds in 2000–2020, while the number of adults was generally low and without trends. Rolling window analyses showed that the drop in juveniles started around 1984, and from 1993 onward the median never exceeded seven juveniles/year (25 %-quantile: 0–1; 75 %-quantile: 4–55). Moreover, adult birds advanced their passage on average 0.48 days per year, passing 26 days earlier in 2020 than in 1946. Earlier migration of adults and decreased numbers of juveniles suggest low reproductive output in recent decades. Morphometric data of recaptured birds show that Little Stints on stopover at Ottenby gain fuel at a speed close to the theoretical maximum, strongly indicating that the conditions at the trapping site remain favourable for foraging waders.